Assessing the Impact of Minimum Wage on South Africa's Earnings distribution - Brey, Yaseen (School of Economics, 2019)
The topic of minimum wage has been of interest for a long time and particularly its potential in addressing wage inequality and ultimately improve the livelihoods of the most marginalized. South Africa has high prevalence of inequality and poverty and the minimum wage is touted as a potential mechanism to improve the lives of individuals at the bottom end of the wage distribution. The mainstay of analysis for minimum wage is the impact on employment. To this end, the paper will flesh out the history of minimum wages and contextualize them through their role in improving welfare. In February 2017, the National Economic Development and Labour Council, constituted out of representatives from business, labour and government, signed the national minimum wage agreement. This agreement outlines the basis for instituting a new national minimum wage no later than 1 May 2018. The proposed new minimum wage of R20 per hour is aimed to “improve the lives of the lowest paid workers and begin to address the challenge of wage inequality” (NEDLAC, 2017). Although many sectors are already at this level, significant increases in the private security and domestic workers sector will require a large increase to come up to parity. In terms of the political economy, the African National Congress (ANC) is undergoing significant grappling for power of South Africa’s ruling party. Although it cannot be seen as more than conjecture, it is nevertheless worthwhile to view the national minimum wage as more than just labour reform, but also a bargaining chip for political gain in the 2019 national elections.